Research Trends in Islamic Ecotheology and Environmental Education: A Bibliometric Analysis - Khafifatul Fian; Muhamad Slamet Yahya; Eka Imbia Agus Diartika; Enjen Zaenal Mutaqin; Nurkholis Nurkholis; Retno Farah Meilani Asidik (Smart Society, 2026)
Environmental crises, including climate change, deforestation, ecosystem degradation, and biodiversity loss, have become pressing global challenges that require multidisciplinary approaches integrating ecological awareness with religious and educational perspectives. Among these approaches, Islamic ecotheology has gained increasing scholarly attention by emphasizing human moral and spiritual responsibility toward environmental sustainability. Despite this growing interest, few studies have systematically mapped the intellectual structure, thematic evolution, and emerging research directions of Islamic ecotheology in relation to environmental education. This study aims to map the development of research on Islamic ecotheology and environmental education through a bibliometric analysis of publication trends, country contributions, thematic structures, keyword networks, and emerging research topics. Data were collected from Google Scholar using the Publish or Perish application between January and March 2026. From an initial dataset of 1,120 publications, 556 articles published between 2016 and 2026 were selected based on their relevance to Islamic ecotheology, environmental education, faith-based environmental movements, and tree-planting initiatives. The data were analyzed using VOSviewer through network, overlay, and density visualizations. The findings reveal a substantial increase in publication output over the study period, reaching its peak in 2025. Indonesia emerged as the leading contributor, accounting for 392 publications (70.50%) based on author affiliations. Network visualization identified several interconnected research clusters centered on climate change, environment, education, ecotheology, and religion. Overlay visualization demonstrated a thematic shift from earlier discussions on climate adaptation and mitigation toward more recent topics, including Islamic ecotheology, environmental education, and tree-based conservation initiatives. Density visualization showed that climate change and ecotheology remain dominant research themes, whereas Islamic ecotheology, ecosystem services, and urban green infrastructure represent promising yet underexplored research areas. This study provides the first comprehensive bibliometric mapping of the intersection between Islamic ecotheology and environmental education, offering a clearer understanding of the field's intellectual landscape while identifying emerging themes and future research opportunities that support the integration of Islamic ecological values into sustainability education and environmental practice.